Silicon Affects Plant Stoichiometry and Accumulation of C, N, and P in Grasslands - Hao, Qian; Yang, Shilei; Song, Zhaoliang; Li, Zichuan; Ding, Fan; Yu, Changxun; Hu, Guozheng; Liu, Hongyan (Frontiers in Plant Science, 2020)
Silicon (Si) plays an important role in improving soil nutrient availability and plant carbon (C) accumulation and may therefore impact the biogeochemical cycles of C, nitrogen (N), and phosphorus (P) in terrestrial ecosystems profoundly. However, research on this process in grassland ecosystems is scarce, despite the fact that these ecosystems are one of the most significant accumulators of biogenic Si (BSi). In this study, we collected the aboveground parts of four widespread grasses and soil profile samples in northern China and assessed the correlations between Si concentrations and stoichiometry and accumulation of C, N, and P in grasses at the landscape scale. Our results showed that Si concentrations in plants were significantly negatively correlated (p < 0.01) with associated C concentrations. There was no significant correlation between Si and N concentrations. It is worth noting that since the Si concentration increased, the P concentration increased from less than 0.10% to more than 0.20% and therefore C:P and N:P ratios decreased concomitantly. Besides, the soil noncrystalline Si played more important role in C, N, and P accumulation than other environmental factors (e.g., MAT, MAP, and altitude). These findings indicate that Si may facilitate grasses in adjusting the utilization of nutrients (C, N, and P) and may particularly alleviate P deficiency in grasslands. We conclude that Si positively alters the concentrations and accumulation of C, N, and P likely resulting in the variation of ecological stoichiometry in both vegetation and litter decomposition in soils. This study further suggests that the physiological function of Si is an important but overlooked factor in influencing biogeochemical cycles of C and P in grassland ecosystems.